The contribution of anthropology to the study of Open Dialogue: ethnographic research methods and opportunities - Mosse, David; Baker, Darren; Carroll, Molly; Chase, Liana; Kloocke, Ruth; Wickremasinghe, Kiara; Cramer, Bethan; Pratt-Boyden, Keira; Wuerth, Milena (Frontiers in Psychology, 2023)
When Open Dialogue diversifies internationally as an approach to mental healthcare, so too do the research methodologies used to describe, explain and evaluate this alternative to existing psychiatric services. This article considers the contribution of anthropology and its core method of ethnography among these approaches. It reviews the methodological opportunities in mental health research opened up by anthropology, and specifically the detailed knowledge about clinical processes and institutional contexts. Such knowledge is important in order to generalize innovations in practice by identifying contextual factors necessary to implementation that are unknowable in advance. The article explains the ethnographic mode of investigation, exploring this in more detail with an account of the method of one anthropological study under way in the UK focused on Peer-Supported Open Dialogue (POD) in the National Health Service (NHS). It sets out the objectives, design and scope of this research study, the varied roles of researchers, the sites of field research and the specific interaction between ethnography and Open Dialogue. This study is original in its design, context, conduct and the kind of data produced, and presents both opportunities and challenges. These are explained in order to raise issues of method that are of wider relevance to Open Dialogue research and anthropology.